Droplet Dynamics of Graphene Oxide Suspensions - Quirke, Jennifer (Trinity College Dublin. School of Physics. Discipline of Physics, 2024)
The emergence of printed electronics as an application of Drop on Demand (DoD) inkjet printing has highlighted the importance of understanding the dynamics of this process for non-Newtonian fluids. From jetting to droplet impacts, surface tension and viscosity of printing fluids play a central role in improving the quality and resolution of printed patterns for producing electronic components. Due to the wide range of electrical, thermal and mechanical properties, non-Newtonian 2D nanoparticle suspensions present excellent candidates for such printing applications. We examined the spreading and splashing behaviour of shear-thinning aqueous graphene oxide (GO) suspensions, and show that the most relevant viscosity in this process for these suspensions during spreading is the high-shear viscosity, and that non-Newtonian behaviour does not influence the critical impact velocity, the impact velocity at which a drop transitions from spreading to splashing. We also found no change in the static surface tension of our samples with GO concentration. Motivated by the commercial use of magnetic fields to improve crop irrigation, we also probed the dynamic surface tension of water by studying pinch-off dynamics in the presence of magnetic fields. As surface tension is the dominant driving force in the pinch-off dynamics in inkjet printing, any influence on this property due to a magnetic field effect would present important applications in refining the printing process for aqueous nanoparticle suspensions. We show that there is no change in dynamic surface tension under the influence of uniform and gradient magnetic fields. This study is extended to pinch-off of aqueous GO suspensions and explores the effect of particle concentration on this process, where we observe an increase in concentration results in a slowing of pinch-off.
APPROVED